Ibadan In Ibadan: The University and The City - Toyin Falola (Yoruba Studies Review)
The University has served as the source of intellectual prowess of the nation and has constantly either produced great personalities in different walks of life or added to their scholastic formation or expansion. Second is the beautiful city of Ibadan, which has constantly reminded Nigerians of their heritage and served as a reference point of how progressive the existence of the town and gown can be. It is therefore not erroneous to affirm that the University of Ibadan has contributed to the conditioning of the City and that the City of Ibadan has its own impact on the University. In addition, the two, have been more like the two proverbial elephants, but in this case, the two elephants are interacting rather than fighting and, in particular, making room for the growth of those who are lucky enough to seek refuge under them. The dynamics of the above are quite important to discuss, critique, and, most importantly, enjoy, and appreciate the terranean beauty of this setting.  Therefore, in this essay, I intend to consider only the things that matter on how, first, the university has contributed immensely to the growth of the city, and second, how the University can affect the City and vice versa.  Lastly, how “us” being part of the stakeholders can engage in active roles in ensuring that this great citadel of learning continues to have remarkable impacts on its surroundings. We believe that it is constantly making great strides and the people of Ibadan are imbibing the benefits of having the institution in their City.